Alveolar Hemorrhage in Vasculitis (Primary and Secondary) - Nasser, Mouhamad; Cottin, Vincent (Seminars in Respiratory and Critical Care Medicine, 2018)
Defined by the accumulation of red blood cells into the alveolar space, diffuse alveolar hemorrhage (DAH) is a severe and potentially fatal medical condition requiring careful attention. In contrast to simple extravasation of erythrocytes facilitated by impaired hemostasis or hemodynamic causes, DAH in vasculitis is due to capillaritis, that is, inflammation of capillaries. Dyspnea, hemoptysis, chest infiltrates, and abrupt fall of blood hemoglobin level represent the cardinal features of DAH; yet, hemoptysis is lacking in one-third of cases. Bronchoalveolar lavage, retrieving bright red fluid, is the best diagnostic clue, also excluding infection and other causes of hemoptysis. Although not recommended, lung biopsy is the gold standard for the diagnosis of DAH and pulmonary capillaritis. Pulmonary capillaritis may be primary as in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis or secondary to drugs (especially antithyroid drugs such as propylthiouracil), infections, connective tissue diseases especially systemic lupus erythematosus, or other small vessel vasculitides. Newer toxic causes of drugs of abuse may be difficult to diagnose. Granulomatosis with polyangiitis and microscopic polyangiitis are the most common causes of capillaritis and DAH, whereas DAH is extremely rare in eosinophilic granulomatosis with polyangiitis. When pulmonary capillaritis is not secondary to underlying systemic vasculitis, idiopathic pauci-immune pulmonary capillaritis may be considered, with or without ANCA. Supportive treatment strategy is mandatory in all cases of DAH. Mechanical ventilation and extracorporeal membrane oxygenation may be used in severe cases. Early identification and removal of the putative drug is crucial in drug-induced vasculitis/DAH and may obviate the need for immunosuppressive therapy. High-dose corticosteroids, intravenous cyclophosphamide, and recently rituximab are the mainstay of treatment in vasculitis. Plasma exchange is recommended in anti–glomerular basement membrane disease and in severe DAH associated with systemic lupus erythematosus and is used in selected cases in ANCA-associated vasculitis.
Keywords: diffuse alveolar hemorrhage; pulmonary vasculitis; connective tissue disease; ANCA-associated vasculitis; respiratory failure; rituximab